Human Rights in Maqāṣid al-Sharī’ah al-Āmmah: A Perspective of Ibn ‘Āshūr - Ulul Umami; Abdul Ghofur (Al-Ahkam, 2022)
Sharī’ah is aimed for the goodness of mankind. By extrapolating the evidence from Qur'an and Sunnah. Islamic sharī’ah is believed to be the rules and objectives for the general interest of society and individuals. This paper focuses on the study of the concept of the nature of human rights in the view of Ibn ‘Āshūr in terms of the maqāṣid al-sharī’ah al-āmmah theory. The study is a kind of library research where the researcher collected the library data by reading books or magazines and other sources to collect data from various literatures. He used a qualitative approach by revealing the meaning of information or empirical data obtained from books, scientific or official research reports and from other literatures. This study, finally, found two results. First, there were found all characteristics of the law, the general purpose, and the meaning of sharī’ah as a whole. Second, it was found the meaning of law combined with four epistemological frameworks, namely: al-fiṭrah (religious instinct), al-samāḥah (tolerance), al-musāwah (egalitarian), and al-ḥurriyah (freedom of action). In the legality of al-maqāṣid law, this research contributes to the human rights of Ibn ‘Āshūr’s ijtihād which becomes the principle of humanity.